The performance of phenothiazine-treated cattle. - Moyer, W.A.; Baker, F.H.; Folse, D.S.; Smith, E.F.; Cox, R.F. (Kansas Agricultural Experiment Station, 2011)
The first experiment was conducted during the winter of 1953-54 with 60 heifer calves. The heifers were raised near Snyder, Texas, and delivered to Manhattan .December 1, 1953. The heifers were assigned December17, 1953, as lots of 10 to a series of wintering experiments. The level of parasitism was established during the last two weeks of December. Fecal samples were collected and E.P.G. (egg per gram) counts were made on the composite fecal samples from each lot. Five heifers in each lot were treated with 60 grams (two 30-gram boluses) of phenothazine on January 14, 1954. A second experiment using this same procedure was conducted during the winter of 1954-55, with 70 steer calves that originated in Barber county, Kansas.
Keywords: Beef; Phenothiazine; Gain; Performance